Organisational behaviour - James, P. S. (Pearson India Education Services, 2017)
People are the primary resources of an organisation. Hence, the first edition of Organisational Behaviour by P.S. James focuses on how to help its readers 'create sustainable competitive advantage through people'. It is a comprehensive text with depth and wide coverage that will not only provide a lucid explanation of the concepts discussed but will also help understand the centrality of OB to create sustained competitive advantage and initiate change.